Faktor-faktor yang Mempengaruhi Komitmen terhadap Karir Ditinjau dari Aspek Perbedaan Jender Studi Kasus: Akademisi Perguruan Tinggi Swasta di Yogyakarta - Ninik Sri Rahayu (Universitas Islam Indonesia, 2008)
This research purposed to investigate career commitment of academics’ staff in Private University of Yogyakarta based on gender perspective. A survey was conducted on 109 women and men academics’ staff in Private University of Yogyakarta. The research formulated two hypotheses, Firstly; there are no significant differences in career commitment between women and men academics’ staff in Private University of Yogyakarta. Secondly, wage structure, career development and work-home harmonization have significant impact toward career commitment both partially and simultantly.The Anova results showed that there are no significant differences in career commitment between women and men academics’ staff in Private University of Yogyakarta. This research also showed empirical finding that simultantly, all independent variables (wage structure, career development and work-home harmonization) have significant impact on career commitment with 95% of level confidence. But partially, only career development has significant impact toward career commitment. Career development has the biggest influenced toward career commitment compare to other variables. According that finding, this research recommended that institutions of private university in Yogyakarta need to formulate a career development policy for academics’ staff based on gender views.Keyword: career commitment, career development, wage structure and work-home harmonization